ANALISIS PERENCANAAN PAJAK PENGHASILAN PASAL 21 SEBAGAI UPAYA EFISIENSI PAJAK PENGHASILAN BADAN USAHA PADA PT. ASURANSI ASEI INDONESIA CABANG MANADO - Manangkalangi, Adikodrati M.; Elim, Inggriani; Budiarso, Novi S. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2019)
Tax planning is one of the ways that taxpayers can use to make tax savings, without violating the constitution or the applicable taxation laws. Tax planning is used to anticipate tax evasion, so that the company can be consistent in payments, and also make corporate tax payments efficient. The research objective is to determine whether the application of tax planning methods used by PT. Asuransi Asei Indonesia Manado Branch in streamlining its tax payments, especially on income tax article 21. In this study the type of data used is qualitative data and quantitative data, while for the data source uses primary data, and the analytical method used is descriptive analysis method. Based on the results of the study, it was concluded that more efficient in paying taxes is to use the Gross-Up Method, rather than using the company's current tax planning method, the Net Method. Because the Gross-Up method, the company PT. Asuransi Asei Indonesia Manado Branch will provide tax benefits equal to article 21 income tax withheld from employee income, without the need for fiscal correction and for this case the allowance the company can provide through the Gross-Up Method is as much as Rp. 132,718,489.